The Application of the Imagery Training Model in Improving the Learning Outcomes of Round Off Students of Physical Education Program - Tono Sugihartono; Dian Pujianto; Ike Rahma Ningsih (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the effect of the imagery training model on the process and learning outcomes of the Roundoff Floor Gymnastics. This study used the classroom action research method (Action Research) with a research design including 1) planning 2) action 3) observation and evaluation, and 4) reflection. The subjects of this study were 30 first semester students. The results of the study show that 1) the imagery training model leads to a better and more conducive learning process which was marked by an increase in Academic Learning-time Physical Education (Alt-PE), whose indicators were students actively moving, practicing and being active during the gymnastic learning process, with the effective time increasing from 25.26% to 71.11% for 90 minutes of learning. 2)Imagery training models have a positive influence on learning outcomes, namely improving roundoff skills with a success rate of more than 80% reaching the good and very good categories, the indicators of which are the starting movement, the core Roundoff movement, landing and 1800 body turns can be done well.